Navigating ISIS’s preferred platform: Telegram - Bloom, Mia (Terrorism and political violence, 2019)
Islamic State in Iraq and Syria (ISIS) online recruitment has been the subject of considerable interest by journalists and technology writers, but there has been no scholarly work to date exploring ISIS Telegram channels and chat rooms. Telegram has played an important role in recruitment and coordination in recent ISIS/terror attacks in Europe. Further, Telegram is quickly replacing the group’s online presence on more open platforms such as Facebook and Twitter as these companies aggressively police and shut down ISIS-linked accounts. This research note aims to demystify Telegram, explain how it can be used for research, and discuss some of the addictive qualities associated with user engagement.